1999
DOI: 10.1074/jbc.274.5.2717
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Phospholipase D in Detergent-insoluble, Caveolin-rich Membrane Domains

Abstract: The activation of cellular phospholipase D (PLD) is implicated in vesicular trafficking and signal transduction. Two mammalian PLD forms, designated PLD1 and PLD2, have been cloned, but their cellular localization and function are not fully understood. Here, we report that in HaCaT human keratinocytes, as well as other cell lines, PLD activity is highly enriched in low density, Triton X-100-insoluble membrane domains that contain the caveolar marker protein caveolin-1. Similar to other PLDs, the PLD activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
89
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 64 publications
15
89
0
Order By: Relevance
“…Okamoto et al (41) recently reported the molecular characterization of a phospholipase D isolated from rat heart that is specific for the production of AEA and other N-acylethanolamides. Interestingly, phospholipase D activity has been shown to be enriched in caveolin-rich membranes (42). The biosynthesis of the hydrophobic amide signaling molecule ceramide appears to be compartmentalized to caveolae, establishing a precedence for the localized production of lipid signaling molecules in caveolae (43).…”
Section: Discussionmentioning
confidence: 99%
“…Okamoto et al (41) recently reported the molecular characterization of a phospholipase D isolated from rat heart that is specific for the production of AEA and other N-acylethanolamides. Interestingly, phospholipase D activity has been shown to be enriched in caveolin-rich membranes (42). The biosynthesis of the hydrophobic amide signaling molecule ceramide appears to be compartmentalized to caveolae, establishing a precedence for the localized production of lipid signaling molecules in caveolae (43).…”
Section: Discussionmentioning
confidence: 99%
“…Sciorra and Morris (224) have recently provided evidence that LPP3 but not LPP1 can generate DAG from PA derived from PLD2 degradation of PC in DIGs in HEK 293 cells. Cell specific localization has also been noted with PLD isoforms, where Czarny et al (45) have observed PLD2 is preferentially targeted over PLD1 to caveolae/rafts in Chinese hamster ovary cells, HaCaT human keratinocytes, and U937 cells. Kim et al (127,128), on the other hand, have localized PLD1 to DIGs in 3Y1 rat fibroblasts and COS7 cells.…”
Section: Lpp In Signaling Platformsmentioning
confidence: 98%
“…With both cell lines, a proportion of the LPP activity was found associated with the caveolin-enriched domains. Presence of LPP in caveolae/ rafts was anticipated, since studies with other cells have shown that PLD (44,45,127,128) and LPA and S1P receptors (100) can be found associated with DIGs.…”
Section: Lpp In Signaling Platformsmentioning
confidence: 99%
“…Some reports indicate that PLD1 also localizes to secretory granules, late endosomes, and lysosomes (18, 20 -22). Cell fractionation studies show that PLD1 activity is restricted to caveolin-enriched membranes in some cell lines (23)(24)(25). There is other evidence that PLD1 might localize at the plasma membrane (26,27).…”
Section: Phospholipase D (Pld)mentioning
confidence: 99%